Pulmonary metastasectomy for metastatic head and neck cancer prolongs survival significantly compared to non-surgical therapy. (16th February 2022) - Schlachtenberger, Georg; Doerr, Fabian; Menghesha, Hruy; Heldwein, Matthias B; Lauinger, Patrick; Wolber, Philipp; Klussmann, Jens Peter; Wahlers, Thorsten; Hekmat, Khosro
Abstract: OBJECTIVES: Pulmonary metastasectomy (PM) is an established procedure for selected patients with metastatic head and neck cancer (HNC). Non-surgical therapy in the form of chemo- and immunotherapy and checkpoint inhibitors and radiation therapy are also treatment options. There are no randomized controlled trials comparing PM with non-surgical therapy. Here, we retrospectively compare the long-term survival of patients, undergoing PM with patients receiving non-surgical therapy. METHODS: All HNC patients with pulmonary metastases were included, if the primary HNC was treated curatively and distant metastases, apart from the lungs were excluded. The pulmonary metastases were confirmed by biopsy as metastases of the HNC primary tumour in the non-surgical therapy group. To further clarify that PM prolonged survival, a propensity score-matched analysis was performed. RESULTS: Between January 2010 and December 2020, 62 HNC patients with isolated pulmonary metastases were included in our analysis. Thirty-three underwent PM and 29 received non-surgical therapy. Histology, tumour stage and localization of the primary HNC did not differ between groups. The number of metastases, age and ASA classification did also not differ between the groups. Patients undergoing PM showed significantly better 1- ( n = 31; 93.5% vs n = 19; 65.5%; P = 0.006), 3- ( n = 17; 72.2% vs n = 9; 30.4%; P = 0.004) and 5-year ( n = 10; 53.4% vs n = 4; 20.0%; P = 0.001) survival rates, compared to patients receiving non-surgical therapy. CONCLUSIONS: Patients with pulmonary metastatic HNC undergoing PM had a significantly better overall survival compared to patients receiving non-surgical therapy. Therefore, selected patients should undergo PM to improve survival. Abstract : Head and neck cancer (HNC) is a generic term for carcinomas of the oral cavity, the tongue, the parotid gland, the larynx and the pharynx.